Disinfection of water using vortex diode as hydrodynamic cavitation reactor - Gaikwad, V.; Ranade, V. (Asian Journal of Chemistry, 2016)
Hydrodynamic cavitation offers distinct advantages for water disinfection and wastewater treatment particularly at large scales of operations. Vortex Diode is a fluidic device, which is conventionally used as a leaky non-return valve in nuclear industry. Recently this device was shown to be effective hydrodynamic cavitation device. In the present study, we have investigated use of cavitation in vortex diode for water disinfection application. Escherichia coli contaminated water is treated successfully using vortex diode. The operating parameters desirable for the disinfection are investigated. The performance is evaluated based on the reduction in the colony forming unit (CFU/mL) of E. coli count estimated by standard spread plate method. The presented results will be useful for identifying appropriate operating conditions for using vortex diode to effectively reduce the bacterial load and disinfect water.

Effect of orifice shape on water disinfection efficacy - Gaikwad, V.; Gaikwad, S.; Ranade, V. (Pollution Research, 2016)
Hydrodynamic cavitation offers distinct advantages for water disinfection and waste watei treatment particularly at large scales of operations. For applying hydrodynamic cavitation foi water disinfection/treatment, water stream to be treated is passed through a fluidic device ir which there exists a low pressure region. Cavities are generated in this region when the pressurt falls below vapour pressure (in absence of any dissolved gases). These cavities are then collapsec when they travel to regions of higher pressure and lead to very high shear, temperatures anc pressures in localized regions. These high pressure/temperature as well as high shear facilitati disinfection as well as reduction in chemical oxygen demand, colour and amonical nitrogen in the water. In this work, we have investigated hydrodynamic cavitation generated by five difieren orifices have been studied which have different shapes with same fractional open area and have tested their effectiveness for water disinfection. The efficacy of generated cavitation on wate disinfection was quantified based on measurements of non-pathogenic E. coli colony forminj units (CFU/mL). The presented results and analysis will be useful for designing hydrodynamii cavitation based systems for water disinfection

Real-Time monitoring of biopharmaceutical crystallization: chord length distribution to crystal size distribution for lysozyme, rHu insulin, and vitamin B12 - Pandit, A.; Katkar, V.; Ranade, V.; Bhambure, R. (Industrial and Engineering Chemistry Research, 2018)
This investigation is focused on designing an effective strategy for the real-time monitoring of biopharmaceutical crystallization using focused beam reflectance measurement (FBRM). Lysozyme, rHu insulin, and vitamin B12 were selected as model biopharmaceutical molecules for the study. Under selected experimental conditions, lysozyme exhibits polymorphism with tetragonal and needle-shaped crystals, rHu insulin forms rhombohedral crystals, and vitamin B12 forms polyhedral-shaped crystals. Focused beam reflectance measurements were performed to obtain the real time chord length distribution (CLD) of crystals obtained using static and dynamic conditions. Mathematical models were developed for converting CLD data obtained using FBRM measurements into the useful crystal size distribution (CSD) data for low (tetragonal, rhombohedral and polyhedral) and high aspect ratio crystals (needle). For high-aspect-ratio crystals, both width-based and length-based models were developed for capturing the CSD. The model validation was performed by comparing the model CSD with the CSD obtained using microscopic image analysis. Developed models effectively capture the CSD for variable shape crystals of lysozyme, rHu insulin, and vitamin B12. It was demonstrated that in the case of high-aspect-ratio crystals, there is an intrinsic limitation in using FBRM for length-based crystal size measurement.

Kinetics of cinnamaldehyde hydrogenation in four phase system - Khan, M.; Joshi, S.; Ranade, V. (Chemical Engineering Journal, 2019)
The kinetics of cinnamaldehyde hydrogenation in four phase system viz. gas (hydrogen)-liquid (cinnamaldehyde + toluene)-liquid (aqueous KOH)-solid (catalyst, 5% Pt/C), [GLLS] system has been studied in this work. As reported, addition of aqueous alkali in hydrogenation of unsaturated aldehydes like cinnamaldehyde shifts selectivity towards unsaturated alcohol, cinnamyl alcohol. The promotion action by alkali metals for improving selectivity towards cinnamyl alcohol involves changes in the adsorption mechanism of the cinnamaldehyde in a way that CO bond get preferentially hydrogenated. In cinnamaldehyde hydrogenation in presence of promoters two different catalytic sites can be considered, each for CO and CC bond hydrogenation. In accordance with this consideration and as demonstrated in various studies on hydrogenation of unsaturated aldehydes, further hydrogenation of intermediate-cinnamyl alcohol (CC bond hydrogenation) occurs on Pt only sites while cinnamaldehyde and intermediate hydrocinnamaldehyde (both involving CO bond hydrogenation) are hydrogenated on catalytic sites affected by promoters. This preferential adsorption and hydrogenation through CO bond leads to the increased selectivity of cinnamyl alcohol. Although, many authors have studied cinnamaldehyde hydrogenation using various promoters, there are very few reports on kinetics in which this two site approach behind promotion action has been considered. The effect of various operating parameters on the rates of hydrogenation was studied and the two site Langmuir-Hinshelwood type of kinetic model was used for evaluating the kinetic parameters by fitting experimental data. The thermodynamic model for estimating the solubility of hydrogen in the reaction mixture was incorporated with this kinetic model.